2013
DOI: 10.1136/archdischild-2012-303244
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the infant car seat challenge and the polysomnogram at the time of hospital discharge

Abstract: The ICSC has a low negative predictive value (0.45) when compared with the PSG as a reference standard for identifying adverse cardiorespiratory events. Although less time consuming and cumbersome than extended polysomnography, the ICSC is not a reliable substitute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Schutzman et al 28 performed a retrospective analysis of preterm infants comparing continuous PSG for 12 to 24 h within 48 h of discharge to a 60 min ICSC. Of the 313 infants who had PSG and an ICSC, 56.5% failed the PSG, defined as apnea 420 s, bradycardia o80 for 3 to 5 s and desaturation o 85% for 3 to 5 s, or evidence of reflux on pH probe.…”
Section: Icsc In Term Infantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Schutzman et al 28 performed a retrospective analysis of preterm infants comparing continuous PSG for 12 to 24 h within 48 h of discharge to a 60 min ICSC. Of the 313 infants who had PSG and an ICSC, 56.5% failed the PSG, defined as apnea 420 s, bradycardia o80 for 3 to 5 s and desaturation o 85% for 3 to 5 s, or evidence of reflux on pH probe.…”
Section: Icsc In Term Infantsmentioning
confidence: 99%
“…9 This evidence also demonstrates the increased risk of Hb-O 2 desaturation events with increased More recent prospective studies have had a variety of Hb-O 2 saturation failure cutoffs, generally between 85 and 90%, with 90% remaining the most commonly used cutoff in published literature. [27][28][29][30][31][32][33] The wide range in the literature reflects the wide ranges used in clinical practice, making many studies difficult to generalize.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[1][2][3] Published CSTS failure rates range from 4.2% to 83%, although the population of infants undergoing screening and the criteria for failure vary across sites. [4][5][6][7][8][9][10] Higher failure rates among infants in the nursery compared with the NICU have been reported. 4,11,12 Other infant characteristics, such as gestational age (GA), race, low birth weight (BW), and sex, have been inconsistently associated with failure.…”
mentioning
confidence: 99%
“…Recent studies confirmed that some infants, including full term babies, experience transient cardiorespiratory abnormalities when positioned in a car seat. 1418 However, no studies have determined whether CSTS accurately identifies infants who are unsafe for transport in a car safety seat and results in subsequent pre-discharge care that prevents later morbidity or mortality among those who fail screening. 11, 12, 19 Moreover, there is limited multicenter data describing the basic epidemiological characteristics of CSTS including the incidence of and risk factors for test failure.…”
mentioning
confidence: 99%